Serological study against transmissible gastroenteritis (TGE) virus in several area in Indonesia - Sendow, Indrawati; Syafriati, Tatty; Bahri, Sjamsul; Sarosa, Antonius (Indonesian Animal Sciences Society, 1998)
A number of 1,168 pig and dog sera from 8 provinces in Indonesia were tested serologically for transmissible gastroenteritis (TGE) antibodies using serum neutralisation test to detect the prevalence of TGE in Indonesia. The sera were obtained from serum bank at Research Institute for Veterinary Science, Bogor. All sera collected before 1995 were negative antibody to TGE. However, sera collected from 2 provinces Sumatera Utara and Sulawesi Utara in 1996 had antibodies against TGE virus (14.03%). Titration of reacted sera showed varied between titres of 8 to 128. Â Key words: Transmissible gastroenteritis virus, serum neutralization test